Respuesta :
Answer:
x = 6
Step-by-step explanation:
[tex]\frac{1}{2}[/tex]x = [tex]\frac{3}{4}[/tex](x-2)
simplify:
[tex]\frac{x}{2}[/tex] = [tex]\frac{3(x-2)}{4}[/tex]
multiply both sides by 4:
2x = 3(x-2)
expand:
2x = 3x - 6
subtract 3x from both sides:
-x = -6
divide both sides by -1:
x = 6
Answer:
x = 6
Step-by-step explanation:
1/2x = 3/4(x-2)
x/2 = 3/2^2(x-2)
x/2 = 3(x-2)/2^2
2x = 3x - 3 x 2
2x = 3x - 6
2x + (-3x) = (3x - 6)
-x = (3x - 6) - 3x
-x = 3x - 6 - 3x
-x = 3x - 3x - 6
-x = -6
x = 6